2014
DOI: 10.1093/glycob/cwu082
|View full text |Cite
|
Sign up to set email alerts
|

In vitro biological characterization of IFN- -1a major glycoforms

Abstract: Recombinant human interferon β-1a (IFN-β-1a) is extensively used as the first-line treatment of relapsing forms of multiple sclerosis. Its glycosylation is recognized as having a complex impact on a wide range of molecule characteristics and functions. The present study reports the enrichment of IFN-β-1a glycoforms and their physicochemical and biological characterization by means of electrospray ionization-mass spectrometry, sialic acid content, thermal denaturation and various in vitro bioassays (antiprolife… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…However, R27T also exhibited considerable variability in its glycoprofile, with tri- and tetra-antennary glycans, as well as bi-antennary glycan forms being detected. Surprisingly, rhIFN-β containing a larger proportion of higher antennary glycoforms showed more sustained bioactivity over time . Indeed, in our previous study, R27T exhibited more prolonged signaling than the mono-glycosylated rhIFN-β, with altered receptor-binding kinetics .…”
Section: Results and Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, R27T also exhibited considerable variability in its glycoprofile, with tri- and tetra-antennary glycans, as well as bi-antennary glycan forms being detected. Surprisingly, rhIFN-β containing a larger proportion of higher antennary glycoforms showed more sustained bioactivity over time . Indeed, in our previous study, R27T exhibited more prolonged signaling than the mono-glycosylated rhIFN-β, with altered receptor-binding kinetics .…”
Section: Results and Discussionmentioning
confidence: 73%
“…Surprisingly, rhIFN-β containing a larger proportion of higher antennary glycoforms showed more sustained bioactivity over time. 42 Indeed, in our previous study, R27T exhibited more prolonged signaling than the mono-glycosylated rhIFN-β, with altered receptor-binding kinetics. 15 A larger portion of higher antennary components in R27T may therefore influence the cellular signaling effects.…”
Section: ■ Introductionmentioning
confidence: 88%
“…The results further confirmed the identity of the 19 and 27 kDa bands as unglycosylated and glycoylated HuIFNβs, respectively. IFNβ is a 166‐amino acid glycoprotein with a single N‐linked carbohydrate chain on Asn80Residue . Heterogeneous mannan residues are added at Asn‐linked glycosylation sites for glycoproteins secreted by K. lactis .…”
Section: Resultsmentioning
confidence: 99%
“…For example, an N-linked glycan on residue 80 of IFN-β-1a has been reported to stabilize the IFN-β-1a structure (Runkel et al, 1998a), and the R27T structure can be stabilized by the hydrogen bond between 35R and N25-linked glycan moieties (Song et al, 2014). It has been reported that the individual glycoforms of IFN-β-1a enable to affect the alternation in biological activities (Mastrangeli et al, 2014). In addition, the glycan enables to decrease the flexibility of the protein backbone and increase protein conformation stability (Wormald and Dwek, 1999).…”
Section: Discussionmentioning
confidence: 99%